1987
DOI: 10.3109/10826088709027425
|View full text |Cite
|
Sign up to set email alerts
|

AIDS and Self-Organization among Intravenous Drug Users

Abstract: Gays and intravenous (i.v.) drug users are the two largest risk groups for AIDS. Gays, unlike drug users, have formed many organizations to deal with AIDS. Data are presented indicating that gay individuals have more risk-reducing behavioral changes than have i.v. drug users. It is also shown that i.v. drug users are more likely to protect themselves if their acquaintances do so. It is suggested that collective self-organization can lead to peer support for risk reduction and that this can help i.v. drug users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(57 citation statements)
references
References 10 publications
0
56
0
1
Order By: Relevance
“…Early in the HIV/AIDS epidemic, research on drug use patterns demonstrated the relationship between adolescent drug use and peer influence (Brooks et al, 1989;Elliot et al, 1985;Friedman et al 1987). In a study of behavior change among IDUs in four countries (Brazil, Thailand, Scotland, and the U.S.), talking about AIDS with drug using friends was consistently associated with reduction in self-reported risk behaviors (Des Jarlais et al, 1995).…”
Section: Network-oriented Interventionsmentioning
confidence: 96%
“…Early in the HIV/AIDS epidemic, research on drug use patterns demonstrated the relationship between adolescent drug use and peer influence (Brooks et al, 1989;Elliot et al, 1985;Friedman et al 1987). In a study of behavior change among IDUs in four countries (Brazil, Thailand, Scotland, and the U.S.), talking about AIDS with drug using friends was consistently associated with reduction in self-reported risk behaviors (Des Jarlais et al, 1995).…”
Section: Network-oriented Interventionsmentioning
confidence: 96%
“…[16][17][18] Using a mixedmethod approach, Friedman et al conducted an exploratory assessment of the relationship between IDU behaviors and the behaviors of their drug acquaintances. 19 The results indicated significant unadjusted relationships between participants_ and acquaintances_ needle sharing and use of cleaned or sterile needles.…”
Section: Introductionmentioning
confidence: 94%
“…Various studies, 1,4-13 including a long-term cohort study in the Bronx, have monitored a pattern that began with rapid spread of the virus during the late 1970s through the early 1980s. Early studies 14,15 indicate that IDUs had become aware of AIDS risk; by 1983, they had begun to reduce risk behavior. During the 1980s, there were approximately 10 years between HIV infection and diagnosis of AIDS.…”
Section: Introductionmentioning
confidence: 99%